Transactive Control of Coupled Electric Power and District Heating Networks - Maurer, Jona (Karlsruher Beiträge zur Regelungs- und Steuerungstechnik, 2023)
The design of approaches for future market-based energy network operation faces the technical challenge of needing to coordinate a vast number of network participants spatially and temporally, in order to balance energy supply and demand, while achieving secure network operation. To meet this challenge, the research field of transactive control emerged. Within this work a new transactive control approach for coupled electric power and district heating networks is presented.